An alternative cytoplasmic domain of the integrin beta 3 subunit. - van Kuppevelt, T H (1989)
A cDNA encoding a new form of the shared beta subunit (beta 3) of the platelet integrin gpIIb/IIIa and the vitronectin receptor was isolated from a placental cDNA library by screening with a beta 3 (gpIIIa) DNA probe. This beta 3 variant differs from the previously reported beta 3 in that the cytoplasmic domain is 8 amino acids shorter and has an alternative, 13-amino acid COOH-terminal peptide. The 3' untranslated region of the cDNA also differs from the previously reported sequence, while the region coding for the transmembrane domain and extracellular domain is identical to it. Reverse transcription combined with polymerase chain reaction was used to show that human placental tissue and two human cell lines contain the variant mRNA. The sequences of the cDNAs for the previously known beta 3 and the variant beta 3 described here suggest that the difference between the cytoplasmic domains of these subunits arises as a result of an alternative mRNA splicing. These cytoplasmic domains may provide alternative means for the beta 3 integrins to interact with cytoskeletal components.